(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2025)
Marine litter is a worldwide concern because of its negative impact on coastal and marine ecosystems due to anthropogenic pressure. Despite implementation of the Marine Strategy Framework Directive (MSFD 2008/56/EC) there is an inability for national monitoring to cover all significant areas in particular Descriptor 10, indicator D10C1 ’’Beach macrolitter’’. This study represents marine litter accumulation and distribution on Durankulak shoreline, Bulgarian North East Black Sea coast. Through regular monitoring along a fixed sampling unit by an unmanned aerial vehicle (UAV) to acquire georeferenced images of the coastline, the report provides detailed data on seasonal variability of accumulation, abundance and typology of beach macrolitter. Marine litter accumulation surveys were carried out in four seasons from May 2024 to January 2025. Marine debris was collected, quantified and categorized in order to determine its abundance, composition and seasonal variations in accumulation rates. The results showed that accumulation alters from 183 to 600 items per 100 m section in different seasons. Total number of items recorded is 2821, with a total amount of 67.887 kg. Marine litter was classified in to eight main categories ’’Artificial polymer materials’’ (90.18% of total number of items), ’’Rubber’’ (2.52%), ’’Cloth/ Textile’’ (0.78%), ’’Paper/ Cardboard’’ (0.96%), ’’Processed/ Worked wood’’ (1.31%), ’’Metal’’ (2.16%), ’’Glass/ Ceramics’’ (1.95%), and ’’Unidentified’’ (0.14%). Significant amount of marine litter collected was of transborder origin. The results shows that there was variation on aggregation and composition of beach litter. Predominant category is „Artificial polymer materials“ and that trend remains unchanged in a seasonal plan.